Macrosomia Risk Factors and Perinatal Outcomes: A 1-year Cohort Study - Isaku, Merita; Vrapi, Enxhi; Cala, Ina; Perdja, Kizjona; Bimbashi, Astrit (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: This study aims to identify possible risk factors and concurrently investigates how macrosomia impacts mothers and neonates. STUDY DESIGN: The study is a retrospective cohort of data obtained in a large tertiary obstetrics and neonatal unit over 1 year, from anuary 1, 2019 to December 31, 2019. Data of all deliveries conducted at the institution were accessed. In addition, singleton and term pregnancies were included for further analysis. Multiple pregnancies, premature births, stillbirths, non-vertex presentations, and being lost to follow-up served as exclusion criteria. A database of the cases was constructed and data regarding maternal constitutional parameters, mode of delivery, shoulder dystocia, perineal trauma, and postpartum hemorrhage were collected. Further on, pregnancies were divided accordingly into two groups: Macrosomic fetuses (>4000 g) and non-macrosomic fetuses (<4000 g). The two groups were compared to assess possible macrosomia risk factors and maternal-neonatal outcomes. Statistical analysis is done using the Mann–Whitney-U and Chi-square tests. Significance was set as p < 0.05. RESULTS: A total of 3408 deliveries met the inclusion criteria of the study. The macrosomia rate is 10.3%. The mean age (30.1 ± 5.17 years vs. 28.9 ± 8.4 years, p < 0.05) and, body mass index (29.2 ± 3.54 vs. 26.1 ± 2.78, p < 0.05) was significantly higher in the macrosomia group. Women that gained more than 12.5 kg have nearly twice the odds of delivering a big baby (odds ratio [OR] 1.86, confidence interval [CI] 1.47–2.36, p < 0.001). No statistically significant differences were noted regarding cases of gestational diabetes (p = 0.56). Cesarean sections were preferred to vaginal deliveries in the macrosomic group (39.3% vs. 29.7%, OR 1.53, CI 1.2–1.9, p = 0.001). The risk of undergoing an emergency procedure is 6-fold higher in pregnancies with macrosomic newborns (20.5% vs. 13.6%, OR 6.1, CI 4.45–8.36, p < 0.001). Both episiotomy rate (40.45% vs. 31.9%, OR 1.44, CI 1.15–1.81, p = 0.001) and lacerations (3.13 % vs. 1.44%, OR 2.21, CI 1.13–4.33, p = 0.02) were higher in the macrosomic group. CONCLUSION: The study concludes that macrosomia is associated with an increase in maternal and neonatal adverse outcomes.